1995
DOI: 10.1098/rspb.1995.0188
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific expression of theα9 n-ACh receptor subunit in auditory hair cells revealed by single-cell RT-PCR

Abstract: Single-cell reverse transcription polymerase chain reaction was carried out in three different cell types from the organ of Corti of the four-day old rat. For this purpose, pieces of the organ of Corti were mounted under a differential-interference contrast video microscope. Two different mounting configurations were used to allow imaging of cells from two almost orthogonal angles. This method afforded unequivocal recognition of various cell types in the vital tissue, and extraction of nucleus and cytoplasm of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…It has yet to be shown whether any of these receptors are localized to the synaptic region of the OHCs, although it is conceivable that they are since they are present in the neurons. If not, another possibility is that an unusual receptor variant is present, as is the case for the acetylcholine receptor of the efferent synapse on OHCs (Glowatzki et al 1995). Thus, although GLAST is concentrated around the OHC bases and the afferent synapses have ultrastructural characteristics suggesting that they are active, other components of functional synapses have yet to be demonstrated conclusively.…”
Section: Fig 5 Graphs Based On the Preliminary Analysis Of Completementioning
confidence: 99%
See 1 more Smart Citation
“…It has yet to be shown whether any of these receptors are localized to the synaptic region of the OHCs, although it is conceivable that they are since they are present in the neurons. If not, another possibility is that an unusual receptor variant is present, as is the case for the acetylcholine receptor of the efferent synapse on OHCs (Glowatzki et al 1995). Thus, although GLAST is concentrated around the OHC bases and the afferent synapses have ultrastructural characteristics suggesting that they are active, other components of functional synapses have yet to be demonstrated conclusively.…”
Section: Fig 5 Graphs Based On the Preliminary Analysis Of Completementioning
confidence: 99%
“…Moreover, in mice lacking GLAST, baseline perilymphatic glutamate levels are elevated compared with controls, and noise overstimulation results in a considerable and sustained increase in glutamate concentration that does not occur in normal mice expressing GLAST (Hakuba et al 2000). In fact, noise overstimulation (Robertson 1983), aminoglycoside antibiotics (Hackney et al 1992), and hypoxia (Pujol et al 1991) all cause afferent nerve terminals at the IHC base to swell, producing damage which resembles excitotoxic changes in the brain. Noise overstimulation also produces terminal swelling to a greater extent in mice lacking GLAST than in normal mice, and this damage is less reversible (Hakuba et al 2000).…”
Section: Role Of Glast In Prevention Of Excitotoxicitymentioning
confidence: 99%
“…Mutations in Brn3.1 (DFNA15) were shown to cause familial adult onset progressive hearing loss in humans (Vahava et al, 1998). Later, HCs express unique ␣9 and ␣10 subunits of the nicotinic acetylcholine receptor (␣9 and ␣10 AChRs; Elgoyhen et al, 1994Elgoyhen et al, , 2001Glowatski et al, 1995). Several other genes are expressed exclusively by HCs, including myosin VIIA (Hasson et al, 1997), parvalbumin 3 (PV3, Heller et al, 2002), and the Notch ligand jagged-2.…”
Section: Markers Of Hc and Scmentioning
confidence: 99%
“…Using immunohistochemistry techniques, Luebke et al reported that in chinchillas, rats and guinea pigs, immunoreactivity to the α9 AChR was confined to calyces around VHC I and the synaptic pole of VHC II [19] . The single cell reverse transcription polymerase chain reaction (RT-PCR) technique has higher sensitivity than the in situ hybridization technique and immunohistochemistry techniques, particularly in studies aimed to localize the cell specific expression of receptors in an individual cell [27] . With the single cell RT-PCR technique, the cell specific expression of α9 AChR in auditory hair cells has been reported [27] .…”
Section: Introductionmentioning
confidence: 99%
“…The single cell reverse transcription polymerase chain reaction (RT-PCR) technique has higher sensitivity than the in situ hybridization technique and immunohistochemistry techniques, particularly in studies aimed to localize the cell specific expression of receptors in an individual cell [27] . With the single cell RT-PCR technique, the cell specific expression of α9 AChR in auditory hair cells has been reported [27] . With the single cell RT-PCR technique, Lustig et al demonstrated the expression of α9 AChR mRNA in both the VHC I and VHC II of chicks [18] .…”
Section: Introductionmentioning
confidence: 99%